Ethnology of the Proximate. The Poetics and Politics of Contemporary Fieldwork - Čapo Žmegač, Jasna (Array, 2006)
This is an introductory text to the volume dealing with contemporary fieldwork in ethnology/ cultural anthropology. The authors discuss field practices in Croatian ethnology and present their view of ethnology/ cultural anthropology as an empirical science seeking to gain insight through fieldwork. They also discuss some features of ethnology of the proximate and contemporary life, especially with respect to the researchers' auto-refelexivity. In the last part they consider the researched group as the readers of their work, and some ethical issues.